On the Sine-Gordon Equation with a Self-Consistent Source of the Integral Type - Khasanov, A. B.; Urazboev, G. U. (Журнал математичної фізики, аналізу, геометрії, 2006)
It is shown that the solutions of the Sine-Gordon equation with a source of the integral type can be found by the method of the inverse scattering problem for the Dirac type operator on the real line.Mathematics Subject Classification: 37K40, 37K15, 35Q53, 35Q55.